Trabalho doméstico: uma análise das condições de trabalho das empregadas domésticas sindicalizadas do município de João Pessoa-PB - Barbosa, Luciana Cândido (2013)
This essay aims to study domestic employment in João Pessoa city in order to investigate the working conditions of unionized housekeepers in the labor market in the city of João Pessoa, the difficulties faced in the workplace and to lesser qualifications and remuneration of those employed are settled in the permanence of sexism, racism and poverty in society. Presents the historical context of gender category and feminism in Brazil, a critical reading of the sexual division of labor, a reflection about domestic work in Brazil and specifically in Paraiba, pointing some legal goals and union struggles. The research reveal that the devaluation of domestic work in João Pessoa is permeated by gender discrimination, social class and race / ethnicity that are intertwined with each other, as structural dimensions of social reality. Thus, research about housekeepers in João Pessoa indicated the same category challenges in Brazil, such as the exploitation of the working day, the double shift and informality, revealing a inferior and enslaved job. However, there is recognition of domestic work as a worthy and decent profession by these workers. This research helped to subsidize the academia data through about the domestic work reality in Joao Pessoa - the union of the maids, the social movement and feminist with data regarding (housekeepers employment socioeconomic conditions affiliated to the Union of Workers and Housekeepers in the city of João Pessoa. Besides collaborating with reflections on gender inequalities and work in this middle in Social Service.